A 900-Year Isotopic Proxy Rainfall Record from Northeastern Botswana - Iain Robertson (Forests, 2023)
A high-resolution climate archive was reconstructed based on carbon isotope analysis and radiocarbon dating of the Chapman baobab in northeastern Botswana. The Chapman baobab, which exhibited an open ring-shaped structure composed of six stems, collapsed in January 2016 during an intense El Niño event. Two samples belonging to the oldest stems were investigated in order to obtain a proxy rainfall record, which provides insight into the precipitation regime over the last millennium, evincing centennial and decadal scale variability. The results indicate that the Medieval Warm Period was marked by relatively stable precipitation, whereas rainfall variability and drought frequency increased during the Little Ice Age. The investigated area has experienced both wetter and drier conditions in the past. The wettest conditions of the last millennium were registered before 1450 while the driest period occurred in 1835. For southern Africa, inter-annual rainfall variability is mainly associated with sea surface temperatures in the Agulhas Current core region, which determine the east–west displacement of tropical temperate troughs. Previous studies suggested that positive sea surface temperature anomalies in the Mozambique Channel led to an eastward movement of the troughs but the Chapman record demonstrates a westward displacement in the past, causing drought in northeastern South Africa and wetter conditions in the central part of southern Africa. The positive rainfall correlation with SST anomalies reversed after 1900, causing a gradual decrease in precipitation and confirming the current aridity trend for Botswana. The results contribute to a better understanding of the past climate of southern Africa for which paleoclimate reconstructions remain scarce.